Does the liberalization of trade advance gender equality in schooling and health? - T. Paul Schultz (Institute for the Study of Labor (IZA), 2006)
This paper assesses the empirical relationship between the liberalization of international trade and the economic status of women. Although historically globalization is not generally linked to the advancement of women, several recent country studies find export led growth in middle and low income countries is associated with improvements in women's employment opportunities. Does intercountry empirical evidence confirm this association across a wider range of countries, and suggest the mechanisms by which it operates? Measures of wages for men and women are an unreliable basis for study of gender inequality in many low income countries, and thus schooling and health are analyzed here as indicators of productivity and welfare and gender gaps. For a sample of 70 countries observed at five year intervals from 1965 to 1980, tariff, quota, and foreign exchange restrictions are found to be inversely associated with trade, and with the levels of education and health, especially for women. Natural resource exports, although providing foreign exchange for imports, appear to reduce investments in schooling and health, and delay the equalization of these human capital investments between men and women. Liberalization of trade policy is consequently linked in the cross section to increased trade, to greater accumulation of human capital, and to increased gender equality.
Keywords: F02; I12; J16; I21; 330; trade liberalization; schooling; health; gender equality; Globalisierung; Internationale Wirtschaftsbeziehungen; Internationale Handelspolitik; Außenhandelsliberalisierung; Gleichberechtigung; Bildungschancen; Gesundheitsversorgung; Welt